Viral Hepatitis: Host Immune Interaction, Pathogenesis and New Therapeutic Strategies. - Quirino, Ângela (2024)
"Magna Græcia" University of Catanzaro "Renato Dulbecco" Teaching Hospital. Unit of Clinical Microbiology, Department of Health Sciences. Catanzaro, Italy.